Aspect Clinique Atypique De La Tuberculose Oculaire A Propos D’un Cas - Nassik, Samia; Masmoudi, Aouatef; Nafizy, Salssabile; Mouine, Saad; Kouisbahi, Amine; Berraho, Amina (European Scientific Journal, ESJ, 2018)
Introduction: The ophthalmological manifestation of tuberculosis varies significantly, and almost all the elements of the globe and orbit can be reached. Methods and Results: The aim of this work was to report a clinical aspect of ocular tuberculosis in a young woman who has a notion of tuberculous contagion and who was presented at the fundus of a macular papillary membrane with a tubercle of Bouchut or papillary tubercle. The diagnosis was retained on a bundle of clinical, biological, and radiological arguments. The evolution under treatment was favorable with an improvement of its visual acuity. Conclusion: It is necessary to know how to evoke the tuberculous etiology in view of all ocular inflammation, even atypical. This is required considering the great polymorphism of its clinical characteristics.